Hemoptoe - Rifanul Ahyana; Martunis Martunis (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Coughing up blood or hemoptysis is expectoration of blood due to bleeding in the airway below the larynx or bleeding that comes out through the airway below the larynx. The incidence of hemoptysis in lung clinics ranges from 10 to 15 percent and for countries with a high incidence of tuberculosis, it is the cause of massive hemoptysis of 20 percent. Meanwhile, 45 percent are caused by bronchiectasis and 10 percent by tumors. The patient, a 64 year old man, came with complaints of coughing up phlegm mixed with odorless blood after the patient cleaned his house. Complaints are accompanied by stabbing pain in the left chest, fluctuating fever, weakness and difficulty sleeping. Eight years ago, the patient took OAT medication for 6 months and was declared cured. On auscultation, crackles were found in the left hemithorax. On chest x-ray, there was an impression of inactive tuberculosis with visible calcification and fibrosis in the right and left lungs. Pulmonary TB is the most common etiology in each classification of hemoptysis. Recurrent hemoptysis occurs more frequently in patients with bronchiectasis, former pulmonary TB and aspergilloma. From the results of the chest x-ray, the impression of inactive TB was also obtained